2003
DOI: 10.1208/pt040213
|View full text |Cite
|
Sign up to set email alerts
|

Poly(D,L-Lactide-Co-Glycolide) microspheres containing 5-fluorouracil: Optimization of process parameters

Abstract: INTRODUCTIONThe objective of this research was to optimize the processing parameters for poly(D,L-lactide-coglycolide) (PLGA) microspheres of 5-fluorouracil (5-FU) and to mathematically relate the process parameters and properties of microspheres. Microspheres were prepared by a water-in-oil-in-water emulsion solvent evaporation technique. A 3 2 factorial design was employed to study the effect of the volume of the internal phase of the primary emulsion and the volume of the external phase of the secondary emu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 17 publications
(14 reference statements)
2
20
0
2
Order By: Relevance
“…Parikh et al also reported the similar results. 19) PLGA concentration in the oil phase is also a key factor influencing the encapsulation efficiency of exenatide microspheres. Exenatide microspheres were prepared using PLGA by varying concentration as given in Table 1 (Formulation F, A and G).…”
Section: )mentioning
confidence: 99%
“…Parikh et al also reported the similar results. 19) PLGA concentration in the oil phase is also a key factor influencing the encapsulation efficiency of exenatide microspheres. Exenatide microspheres were prepared using PLGA by varying concentration as given in Table 1 (Formulation F, A and G).…”
Section: )mentioning
confidence: 99%
“…However, it has been shown that the a high encapsulation efficiency of macromolecular hydrophilic compounds (e.g. peptides, proteins, DNA) in PLGA microspheres can be established by optimizing the formulation parameters, such as type and polymer concentration [10], type and concentration of surfactant [11,12], volume of the internal phase of the primary emulsion, and the volume of the external phase of the secondary emulsion [13]. There are several drawbacks associated with the use of PLGA as a drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike w/o emulsification method, water-in-oil-in-water (w/o/w) emulsion solvent evaporation technique proves much more effective when the aqueous solubility of drug is high (>900 mg/ml) and partitioning into the organic phase is disfavorable (6). Accordingly, microspheres containing water soluble drugs have been prepared using different polymers such as poly(lactide-co-glycolide) (PLGA) (7), eudragit RS (8), polymethyl methacrylate (9). In addition, modified procedures of this technique have been proposed to obtain desired properties of the microspheres, loaded with the water soluble active principles.…”
Section: Introductionmentioning
confidence: 99%